Migrant returns Manila, development, and transnational connectivity - Pido, Eric J.
Eric J. Pido examines the complicated relationship between the Philippine economy, Manila’s urban development, and Filipino migrants visiting or returning to their homeland, showing migration to be a multidirectional, layered, and continuous process with varied and often fraught outcomes.